2011
DOI: 10.4236/nm.2011.24039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Influencing Medication Adherence in Patients with Epilepsy in Rural Communities of Kaduna State, Nigeria

Abstract: Background and Objective: Adherence to medication is the backbone to effectiveness of a therapy. In the absence of a definitive curative therapy, antiepileptic therapy is a key intervention aimed at prolonging and improving the quality of life of patients with epilepsy (PWE) who suffer from a disease known for its stigmatization with many cultural misconceptions. The aim of the study is to assess the level of, and factors influencing adherence to antiepileptic therapy among patients in rural communities attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 7 publications
(9 reference statements)
9
23
3
1
Order By: Relevance
“…gender and age) between AED-adherent and AED-nonadherent patients. A study by Johnbull et al (15) reported a similar observation, in that gender did not affect the adherence rate in their study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…gender and age) between AED-adherent and AED-nonadherent patients. A study by Johnbull et al (15) reported a similar observation, in that gender did not affect the adherence rate in their study.…”
Section: Discussionsupporting
confidence: 64%
“…This finding is in accordance with those of studies conducted by Liu et al (13) and Paschal et al, (24) who reported that the primary reason for nonadherence in their study cohort was forgetfulness (69.6% and 32.5%, respectively). Johnbull et al (15) observed that forgetfulness was the reason for nonadherence in only 40.7% of their study cohort.…”
Section: Discussionmentioning
confidence: 80%
“…The main therapy related factors in our study include complexity of medication and problems related to therapy like sedation, weight gain, anger, etc. This result was in agreement with Johnbull et al who reported that forgetfulness and drug induced fatigue were the major reasons for poor adherence [6].…”
Section: Ayswarya and Kumarsupporting
confidence: 93%
“…Quality of life (QOL) is a subjective concept based on the subject's perspective and experiences and involves physical, psychological, social and cultural components, all of which contributes to patient's adjustment to his condition and impacts perception in his life [4,5]. The frequency and seizure severity, adverse effects of antiepileptic drugs (AEDs), seizure worry, mood status, physical, cognitive, and psychosocial limitations including dependence of caregivers are determinant aspects frequently assessed by QOL inventories [6]. Medication adherence is the backbone of antiepileptic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of antiepileptic drug nonadherence is ranged from 26% in USA to 67% in Nigeria [7, 8]. As a study done in the North Carolina indicated, the prevalence of AEDs nonadherence was 39% and it was higher (43%) in elderly accompanied with increased likelihood hospitalization [9].…”
Section: Introductionmentioning
confidence: 99%